A preterm girl with big problems – case report with applied nursing procedures - Pasztelan, Małgorzata; Pulikowski, Jarosław; Rybojad, Beata (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Children born prematurely are more prone to severe systemic dysfunctions due to their immaturity. Complications of prematurity include respiratory distress syndrome, intraventricular bleeding, and retinopathy, among others. These conditions entail many med-ical and developmental problems, which pose a major challenge for the therapeutic team. Preterm infants require special and skilled nursing care, which is no less important than medical care. This includes monitoring vital functions, toileting the respiratory tract, or forming a bond between parents and child. The survival, as well as the further development of the child largely depends on the decisions made by the medical staff. Cooperation between doctors, nurses, and parents in the intensive care unit is important to optimise the therapeutic process. In this article, we present the case of a neonate born in the 25 th week of gestational age (foetal gestation), a patient in the Intensive Care Unit with complications of extreme prematurity.